Physicochemical Characterization of Zeolite Materials Produced from Selected Low-Cost Agricultural Wastes - A. A. Nuhu; Z. N. Garba; H. Ibrahim; S. Abdulrazak (Journal of Applied Sciences and Environmental Management, 2024)
Zeolites play a crucial role in adsorption processes for eliminating pollutants from industrial effluents and are extensively utilized in catalytic activities across diverse syntheses. This study focused on the conversion of three agricultural wastes—corncob, groundnut shell, and sugarcane bagasse—into zeolitic materials through three analytical methods: hydrothermal, microwave sintering, and alkali fusion, respectively. Standard methods were employed to assess the physicochemical parameters of the resulting zeolites. Generally, the produced zeolites had excellent surface areas and porosities. However, zeolites synthesized from sugarcane bagasse via the alkali fusion method exhibited highest porosity (80.9%), whereas that derived from corncob demonstrated highest surface area (1335 m2/g). Point of zero charge for the produced zeolites was within the range of 7.9-9.8, with zeolite produced from groundnut shells via alkali fusion having the highest value (9.8). The elevated porosities and surface areas, and point of zero charge of the synthesized zeolites signify their enhanced adsorptive capacity, implying their suitability for application as adsorbents for the removal of organic and inorganic pollutants. These findings underscore the effectiveness of synthesized zeolites in reducing or completely removing pollutants such as phenols, dyes, pesticides, heavy metals, and inorganic anions from wastewater.